Extraction of Noble Metals from Pyrite Cinders - Bagdaulet Kenzhaliyev; Tatiana Surkova; Dinara Yessimova; Zhazira Baltabekova; Yerkezhan Abikak; Bekzat Abdikerim; Zamzagul Dosymbayeva (ChemEngineering, 2023)
When obtaining sulfuric acid from pyrite concentrates, a significant amount of waste is generated in the form of pyrite cinders that require disposal. The methods used in processing this raw material are, as a rule, the pyrometallurgical processes of chlorination and chloride sublimation, the disadvantages of which include increased energy consumption and a lack of complexity in the extraction of valuable components. Hydrometallurgical processes are in less demand due to their multi-stage nature and complexity of execution. The method of chemical activation developed at the JSC “Institute of Metallurgy and Ore Beneficiation” makes it possible to isolate iron and non-ferrous metals into separate, middling products and to concentrate noble metals in the cake at the first stage. Physical and chemical studies of the cake found that its basis comprises iron compounds. The silver in the cake is associated with pyrite, while the gold is associated with hematite; it is also possible to find gold in the form of AuCl3. The content of gold in the cake is 1.5 g/t, and the silver content is 17.7 g/t. Based on physical and chemical studies and data from the literature, various versions of the hydrochlorination method are proposed to open the cake.